Private school canteens: an analysis of the economic and financial aspects of the traditional and the healthy models - Luisa Arantes Vilela; Bruna Vieira de Lima Costa; Mariana Zogbi Jardim; Luiza Delazari Borges; Ariene Silva do Carmo; Monique Louise Cassimiro Inácio; Larissa Loures Mendes (BMC, 2023)
Abstract Background One of the reasons for the more prominent resistance of canteen managers to implementing healthy canteens is based on the belief in the economic infeasibility of these models. The research aimed to verify the economic and financial viability of traditional and healthy models of school canteens in a Brazilian metropolis. Methods The case study was carried out with 36 companies in the school canteen sector in a Brazilian metropolis. The classification of items sold in canteens considered the extent and purpose of food processing according to the NOVA Classification. The characterization and definition of traditional canteens and healthy canteens were proposed considering the amount of in natura or minimally processed foods and culinary preparations without the presence of ultra-processed foods; the percentage of ultra-processed foods or processed foods or culinary preparations with the presence of ultra-processed foods; and the existence of prohibited foods. The economic and financial analysis was carried out mainly through the evaluation of profitability. Data were collected through an electronic self-administered questionnaire sent to canteen managers. The Mann-Whitney test was used to compare medians and the Chi-Square/Fisher's Exact Test to compare proportions. Results The study included six companies, responsible for 36 canteen units in private schools, 30 classified in the traditional model (83.3%), and six in the healthy model (16.7%). The median percentage of natural, minimally processed foods and commercialized culinary preparations was higher among the healthy model canteens (87.9% vs. 60.0%, p < 0.001). While the median percentage of ultra-processed, processed, or preparations with the presence of ultra-processed (40.0% vs. 12.1%, p < 0.001) and prohibited foods (10.0% vs. 0%, p < 0.001) sold was higher in the traditional model canteens. The results indicated that the profitability in the healthy canteens was higher (p < 0.001) than in the traditional ones. Conclusions Healthy school canteens showed better financial and economic results compared to traditional canteens with emphasis on greater profitability and a shorter recovery time of the initial investment.